Transmisi dan Preservasi: Analisis Proses Penurunan dan Kodifikasi Al-Qur’an di Era Awal Islam: Jam’ul Al-Qur’an - Fatima, Nur (Maliki Interdisciplinary Journal, 2025)
This article aims to examine in depth the process of the Qur’an’s revelation to the Prophet Muhammad, as well as identify the stages and scholarly figures involved in writing, collecting and codifying the holy book. Through a historical and analytical approach, this study traces how divine revelation was transmitted, recorded, and finally standardized into the mushaf that we know and use today. The results of this study provide a comprehensive insight into the efforts to preserve the Qur’anic text in the early Islamic era and its relevance for Muslims.